Proposed methodology for the design of flexible pavements using geosynthetics as reinforcement - Jugo, Augusto (2025)
This work presents a design proposal for the design of flexible pavements using geosynthetics to reinforce the granular base materials and protect the subgrade. The proposal was developed by a theoretical-conceptual research work of the use of geosynthetics in pavements. The basis benefits of placing geosynthetics in the subgrade-granular base interface, as a function of the non-linearity response of the materials, is discussed. Considering, the complexity of the problem, the analysis presents logical results that can support to establish the principles for a rational design procedure. The analysis was conducted with the AASHTO-93 Design Procedure, and its concepts.